2022
DOI: 10.1177/02698811211069110
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microglial activation by antidepressants

Abstract: Background: Recent studies have suggested that microglial activation plays a key role in the pathogenesis of depression. In fact, neuroinflammation is associated with a phenotypic change of microglia, consisting of morphological differences, increased release of cytokines and oxidative stress products, which may contribute to the development and maintenance of depression. Antidepressants, including selective serotonin re-uptake inhibitors and serotonin–norepinephrine reuptake inhibitors, have been shown to act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…Patients with a clinical diagnosis of depression are often treated with antidepressants. Some antidepressants can modulate microglial activation that plays a key role in neuroinflammation 30 . Thus, in the patients with a clinical diagnosis of depression, neuroinflammation may not necessarily reflected the CES-D scores.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a clinical diagnosis of depression are often treated with antidepressants. Some antidepressants can modulate microglial activation that plays a key role in neuroinflammation 30 . Thus, in the patients with a clinical diagnosis of depression, neuroinflammation may not necessarily reflected the CES-D scores.…”
Section: Discussionmentioning
confidence: 99%
“…Two isoforms of MAO encoded by MAOA and MAOB genes belong to the family of flavin-containing amine oxidoreductases, showing functional differences for their anatomic localization and major substrate ( Fisar, 2016 ; Shahid Nadeem et al, 2022 ). Previous studies have found that the inhibition of MAO activity can modulate LPS-induced microglial activation in vitro , suppressing the expression of pro-inflammatory factors ( Obuchowicz et al, 2006 ; Dhami et al, 2013 ; Park et al, 2020 ; Mariani et al, 2022 ). Rasagiline Mesylate (RM), a well-known irreversible MAO-B inhibitor, could suppress the expression of pro-inflammatory cytokines in LPS-treated BV2 cells ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies with animal models showed that antidepressants can reduce inflammation and oxidative stress, e.g., inhibitory effects on the expression of inflammatory mediators, including cytokines, as well as on microgliosis and astrogliosis, were detected [ 62 , 63 ]. Some antidepressants act through the same inflammatory and oxidative stress mechanisms commonly reported to be disrupted in depression, and this may represent one of the mechanisms through which they exert additional antidepressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some antidepressants act through the same inflammatory and oxidative stress mechanisms commonly reported to be disrupted in depression, and this may represent one of the mechanisms through which they exert additional antidepressive effects. Because microglia are involved in the regulation of inflammation and oxidative stress, and antidepressants can prevent microglial activation in vitro and in animal models, the inhibition of microglial activation may play an important role, contributing to antidepressive effects [ 62 , 64 ]. Moreover, the inhibition of pro-inflammatory cytokines by antidepressants can contribute to antidepressive behavior, e.g., doxepin prevented stress-induced memory impairments and decreased TNF-α levels in the rat hippocampus, explaining one possible mechanism of pharmacological symptom control by antidepressants [ 54 ].…”
Section: Discussionmentioning
confidence: 99%